Comparing Short and Long Oocyte-Sperm Co-Incubation Periods on in Vitro Developmental Outcomes - Fang Cao; Lingjun Li; Xiuliang Dai; Xiyang Xia; Li Chen; Yufeng Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: This study aimed to compare the effects of different gamete co-incubation times on fertilization, embryo development potential, along with clinical outcomes. Methods: The study included 530 cycles with short co-incubation times (4–6 hours), referred to as the S group, and 1653 cycles with long co-incubation times (16–24 hours), referred to as the L group, all undergoing in vitro fertilization (IVF) without rescue intracytoplasmic sperm injection (R-ICSI). The study analyzed the basic characteristics and clinical outcomes of these two groups. Additionally, the study stratified the cycles based on the number of oocytes retrieved and performed multivariate logistic regression analysis with the normal fertilization (two pronuclei, 2PN) rate as the dependent variable and co-incubation time as the main independent variable. The study also examined 79 partial short co-incubation cycles, dividing them into a short co-incubation part (10 oocytes) and a long co-incubation part (the remaining oocytes), to analyze embryo developmental parameters. Results: There were no significant differences in the rates of top-quality blastocyst formation, clinical pregnancy, and implantation between the two groups (p > 0.05). 2PN rate in S group was slightly lower than in L group (68.06% vs. 71.08%, p < 0.01). After stratifying by the number of oocytes obtained, multiple logistic regression analysis demonstrated no significant correlation between co-incubation time and 2PN rate (p > 0.05). In the 79 partial short co incubation cycles, there were no significant differences in the rates of 2PN oocytes, ≥3PN (3 pronuclei) oocytes, top-quality cleavage embryos, and top-quality blastocysts on Day 5/Day 6 between the two parts (p > 0.05). Conclusions: Short oocyte-sperm co-incubation is an effective strategy in preventing fertilization failure. Short and long oocyte-sperm co-incubation times have similar outcomes on in vitro development.